Detection of pericentric inversion with breakpoint in DMD by whole genome sequencing. Issue 10 (1st August 2022) - Zaum, Ann‐Kathrin; Nanda, Indrajit; Kress, Wolfram; Rost, Simone
Abstract: Background: Dystrophinopathies caused by variants in the DMD gene are a well‐studied muscle disease. The most common type of variant in DMD are large deletions. Very rarely reported forms of variants are chromosomal translocations, inversions and deep intronic variants (DIVs) because they are not detectable by standard diagnostic techniques (sequencing of coding sequence, copy number variant detection). This might be the reason that some clinically and histologically proven dystrophinopathy cases remain unsolved. Methods: We used whole genome sequencing (WGS) to screen the entire DMD gene for variants in one of two brothers suffering from typical muscular dystrophy with strongly elevated creatine kinase levels. Results: Although a pathogenic DIV could not be detected, we were able to identify a pericentric inversion with breakpoints in DMD intron 44 and Xq13.3, which could be confirmed by Sanger sequencing in the index as well as in his brother and mother. As this variation affects a major part of DMD it is most likely disease causing. Conclusion: Our findings elucidate that WGS is capable of detecting large structural rearrangements and might be suitable for the genetic diagnostics of dystrophinopathies in the future. In particular, inversions might be a more frequent cause for dystrophinopathies as anticipated and should be considered in genetically unsolved dystrophinopathy cases. Abstract : We describe the case of a boy suffering from dystrophinopathy due to a pericentric inversion which was detected by Whole Genome Sequencing. The inversion was recognisable in the NGS data with breakpoints in DMD intron 44 and Xq13.3.